PENGEMBANGAN EKONOMI KREATIF EMPING DESA KAMASAN MENGGUNAKAN SISTEM E-COMMERCE - Mochamad Yusuf Romdoni; Irma Yunita Ruhiawati (LPPM Unbaja, 2019)
This research aims to raise the sales pattern of emping production in a kamasan village located in Cinangka sub-district of Serang District so that the creative economy community in the village can maximize the sales process to be more effective and more developed by utilizing a superior e-commerce system in one of the wrong one of the best market places for the nation's children is bukalapak.com, the method of analysis in this development uses data collection techniques through interviews, questionnaires, observation, documentation and tests and at the design stage here using the System Development Life Cycle (SDLC) so that it can provide results measurable and as expected, which can help creative economic actors increase emping production in Kamasan village.